(untitled) (Global Journal of Human-Social Science, 2023)
The purpose of this article is to analyze the State’s conformations in the scope of the financial management of public resources, in the context of capitalism under financial predominance, pointing out its correlation with the consequences of poverty in Brazil. To this end, it analyzes the tax bases that finance social policies in Brazil and the management of social expenses, using data extracted from the Federal Revenue Service of Brazil and the SIGA Brasil system, in the period from 2016 to 2019, corresponding to the beginning of the "New Fiscal Regime" of greater fiscal austerity. The results indicate a higher incidence of taxes on the poorest population, in addition to a significant decrease in actions linked to social policies that are so important in combating poverty, to the detriment of the allocation of public resources for the payment of financial expenses with interest, charges and amortization of the public debt.